The Efficacy of the Mulligan Concept to Treat Meniscal Pathology: A Systematic Review - Nathan C. Reep; Sydney N. Leverett; Rebecca M. Heywood; Russell T. Baker; Darren L. Barnes; Scott W. Cheatham (North American Sports Medicine Institute, 2022)
# Background Meniscal pathologies are common knee injuries and arthroscopic surgery is the current accepted gold standard for treatment. However, there is evidence to support the use of the Mulligan Concept (MC) Mobilization with Movement (MWM) for meniscal pathologies including the 'Squeeze' technique, tibial internal rotation (IR), and tibial external rotation (ER). # Hypothesis/Purpose The purpose of this systematic review was to critically appraise the literature to investigate the effectiveness of MC MWMs for meniscal lesions on patient reported pain, function, and multi-dimensional health status in patients with clinically diagnosed meniscal pathologies. # Study Design Systematic Review # Methods A literature search was completed across multiple databases using combinations of the words "knee, function, mobilization with movement, MWM, mulligan concept, MC, meniscal pathology, meniscal derangement, and meniscal tear." Studies written within the prior 10 years that examined MC MWM techniques to treat knee meniscal injury were included. Articles that met the inclusion criteria (used MC MWM 'Squeeze' technique, tibial IR, or tibial ER for treatment of clinically diagnosed meniscal pathologies; Patient reported outcome \[PRO\] measures had to be used in the assessment of knee pain or function) were analyzed for quality. Randomized control trials were analyzed using the PEDro scale and the Downs & Black (D&B) checklist, case series were analyzed using the Joanna Briggs Institute (JBI) checklist, and case reports were analyzed using the CARES checklist. # Results Six articles met the inclusion criteria and were included in this review, two randomized controlled studies, two case series, and two case reports consisting of 72 subjects. All six papers included reports of improvements in pain and function that were either statistically significant or met the minimal clinically important difference (MCID). Five studies reported the Disablement in the Physically Active (DPA) scale that also demonstrated statistically significant differences or met the MCID. The MC MWM 'Squeeze' technique, tibial IR, or tibial ER demonstrated the ability to reduce pain, improve function, and improve patient perceived disability following treatment of a clinically diagnosed meniscal pathology. These studies demonstrated short term results lasting from one week to 21 weeks. # Conclusion Treatment interventions incorporating MC MWM techniques demonstrated reduction of pain and improvement in function in the short term in patients with clinically diagnosed meniscal pathologies. # Level of Evidence 2a